A Comprehensive Study on Smart City using BlockChain Technology - Raja, Anitha (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IOT) consists of, any devices from sensors to smartphones and wearable technology. IoT is all about data. While the IoT grows, data insecurity also increases. The definition involves small devices each with their own Internet Protocol (IP) address connected to other such devices via the internet. Nowadays every home and every business is connected via the Internet of Things, the next level of technology is to connect the whole city in near future. The objective of smart city is to develop an urban city with fully secured from hackers and malware attackers The IOT is a centralized system where, every source information is stored in a centralized manner which is vulnerable to software attacks and system can easily be hacked. This paper proposes building an IOT Smart city using trustworthy decentralized BlockChain technology.